The Cases of COVID-19 and Measles Co-Infection in Children - N. N. Zvereva; M. A. Sayfullin; E. R. Samitova; L. N. Mazankova; V. G. Akimkin; N. N. Vasilyeva; E. Y. Pylaeva; Y. V. Romanova; A. A. Rakhalina; A. Y. Rtischev; A. E. Angel; O. V. Shamsheva (Эпидемиология и вакцинопрофилактика)
Relevance. The rapid spread of new pathogens inevitably leads to the occurrence of joint circulation with already known infectious agents, leading to the development of mixed infections. The simultaneous circulation of the pandemic coronavirus SARS-CoV-2 with a highly contagious measles virus leads to the development of mixed infections in people who have not been sick or vaccinated against measles. Aims. Review cases of co-infection with measles and COVID-19 in Moscow. Material and methods. A retrospective study of cases of measles and COVID-19 co-infection in three children with a description of the epidemiological and clinical picture of the disease. Results. In all observed children, the manifestation of the disease was typical for measles, the diagnosis of COVID-19 was established based on a laboratory study carried out in a hospital, which gave reason to count. That the infection with SARSCoV-2 occurred after the infection of children with measles. Conclusions. Different incubation periods can lead to several options for the development of co-infection. The similarity of clinical symptoms at the onset of the disease does not allow excluding a certain infection clinically, without laboratory verification.